2, 7‐Dioctylbenzofuro[3, 2‐b]benzofuran: An Organic Semiconductor with Two‐dimensional Transport Channels. Issue 11 (27th September 2018) - Chen, Daoliang; Li, Jie; Ma, Weimin; Li, Baolin; Zhen, Yonggang; Zhu, Xiaozhang; Hu, Wenping; Tsuji, Hayato; Nakamura, Eiichi
Abstract: We report herein a synthesis of benzofuro[3, 2‐ b ]benzofuran (BFBF) by an intramolecular Ullmann C−O coupling reaction. To tune the film forming ability and self‐assembling behaviour, the derivative possessing two alkyl chains, 2, 7‐dioctylbenzofuro[3, 2‐ b ]benzofuran (C8 ‐BFBF), was further prepared. The packing structures of these two compounds were studied by XRD analysis, showing a two‐dimensional (2D) stacking structure in the solid state. DFT calculations indicated that C8 ‐BFBF exhibited large transfer integrals along the two stacking directions. The OFET devices based on C8 ‐BFBF showed typical hole transport properties with mobility up to 0.076 cm 2  V −1  s −1 . Abstract : 2, 7‐dioctylbenzofuro[3, 2‐ b ]benzofuran (C8 ‐BFBF) was synthesized by a new synthetic method. The packing structure of C8 ‐BFBF was studied by XRD analysis, and it shows two‐dimensional (2D) stacking structure in solid state. DFT calculations indicated that C8 ‐BFBF possessed large transfer integrals along the two stacking directions. The OFET devices based on C8 ‐BFBF showed typical hole transfer properties with mobility up to 0.076 cm 2  V −1  s −1 .